Exploring the Impact of YouTube Videos on Improving Listening Skills for EFL Secondary School Students in Sudan - Othman, Khalid (International Journal of Language and Literary Studies, 2023)
This study was carried out with the participation of forty-seven (47) high school students who were required to take English in order to continue their education at the university level. The participants were asked to respond to a given questionnaire composed from (5) axes, each axis has many items, the target was to explore the effect of watching YouTube on listening skills. Their responses were analyzed statistically, the results showed that some students were aware of the importance of listening skills and few do not have the sufficient perception about how these videos can help them. Their ability to interact with the speaker was showed as one of the most required skills, mastering this skill helps the students to interact with speakers. Students' ability to process information has been boosted by watching YouTube videos, and most will speak up if the presenter requests it, but many still struggle to come up with an appropriate answer to what was said, and many more are unable to adapt to differences in delivery style. We recommend watching the videos in the accompanying table.